Ocean Governance Knowledge Systems, Policy Foundations and Thematic Analyses - Partelow, Stefan; Hadjimichael, Maria; Hornidge, Anna-Katharina (MARE Publication Series, 2023)
This Open Access book on Ocean Governance examines sustainability challenges facing our oceans today. The book is organized into three sections: knowledge systems, policy foundations and thematic analyses. The knowledge produced in the book was catalyzed by the scientific outcomes within the European-funded Cooperation in Science and Technology (COST) network "Ocean Governance for Sustainability - Challenges, Options and the Role of Science". This network brings together scientists, policy-makers and civil society representatives from 28 nation states to cooperate on ocean governance research. This book offers a compilation of new research material including focused case studies, broad policy syntheses and reflective chapters on the history and current status of knowledge production systems on ocean governance. New research material is presented, although some chapters draw on secondary sources. The book starts with synthetic review chapters from the editors, outlining past andpresent knowledge systems, addressing how and why ocean governance for sustainability is where it currently stands with critical reflections on existing narratives, path dependencies and colonialist histories. This is followed by chapters addressing, synthesizing and analyzing different legal and policy frameworks for ocean governance both regionally and internationally. At the core of the book are the thematic analyses, which provide focused case studies with detailed contextual information in support of different ocean governance challenges and sustainability pathways around the world. The book concludes with a chapter explicitly targeting students, researchers and policy-makers with key take-away messages compiled by the editors.